ICIPE International Centre of Insect Physiology and Ecology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The International Centre of Insect Physiology and Ecology (ICIPE) was established in Nairobi Kenya in 1970 as an institute for advanced research in insect science and its application. This was at a time when many people were growing alarmed by the...